How decision‐making about euthanasia for animals is taught to Australasian veterinary students. Issue 8 (17th May 2021) - Littlewood, KE; Beausoleil, NJ; Stafford, KJ; Stephens, C; Collins, T; Quain, A; Hazel, S; Lloyd, JK.F; Mallia, C; Richards, L; Wedler, NK; Zito, S
Abstract : This study set out to explore how euthanasia decision‐making for animals was taught to students in eight Australasian veterinary schools. A questionnaire‐style interview guide was used by a representative at each university to interview educators. Educators were interviewed about their teaching of euthanasia decision‐making for four categories of animals: livestock, equine, companion and avian/wildlife. Using thematic analysis, the terms provided by participants to describe how (mode of teaching) and what (specific content) they taught to students were categorised. Information about content was categorised into human‐centred factors that influence decision‐making, and animal‐based indicators used to directly inform decision‐making. All eight representatives reported some teaching relevant to euthanasia decision‐making at their university for livestock, companion animal and avian/wildlife. One representative reported no such teaching for equid animals at their university. Observation of a euthanasia case was rarely reported as a teaching method. Five universities reported multiple modes of teaching relevant information, while two universities made use of modalities that could be described as opportunistic teaching (e.g., 'Discussion of clinical cases'). Factors taught at most universities included financial considerations, and that it is the owner's decision to make, while animal‐based indicators taught included QoL/animal welfare, prognosis and behaviour change. Overall, most universities used a variety of methods to cover relevant material, usually including lectures and several other approaches for all animal types. However, because two universities relied on presentation of clinical cases, not all students at these veterinary schools will be exposed to make, or assist in making, euthanasia decisions.